Self-cleaning functionalized FeNi/NiFe2O4/NiO/C nanofibers with enhanced microwave absorption performance. Issue 9 (15th June 2020) - Shen, Yongqian; Wei, Yupeng; Ma, Jiqiang; Zhang, Yuchen; Ji, Binghan; Tang, Jie; Zhang, Luyin; Yan, Pengze; Du, Xueyan
Abstract: Microwave absorbing materials with enhanced microwave absorption performance and self-cleaning function are of great interest for military applications and human health caused by electromagnetic radiation pollution. Herein we report the synthesis of FeNi/NiFe2 O4 /NiO/C nanofibers (NFs) via electrospinning technique using nickel acetylacetonate (Ni(acac)2 ), ferric acetylacetonate (Fe(acac)3 ), and N, N -dimethylformamide (DMF)/polyacrylonitrile (PAN) solution as precursor. We also show the abilities of the materials to attenuate electromagnetic microwave and their ease of self-cleaning performance. X-ray diffraction patterns and HRTEM images reveal that the materials possess FeNi, NiFe2 O4, NiO and graphite. HAADF-STEM images show that the magnetic nanoparticles distribute uniformly along the fibers. Contrast experiments had been conducted on different calcination temperatures to elucidate the impedance matching and loss mechanism. Based on the results of the experiment, excellent microwave absorption was exhibited by blending the NiFe2 O4 /NiO/CNFs and FeNi/NiFe2 O4 /NiO/CNFs into paraffin at 50 wt% and 5 wt%, respectively. Moreover, the contact angles (CA) of the as-prepared fiber films calcined at 650, 750 and 950 °C were 143°, 141° and 144°, respectively, indicating that fiber films exhibited excellent hydrophobicity and self-cleaning function. It suggested that the as-obtained NFs had an excellent application prospect in self-cleaning microwave absorbing materials.